PENERAPAN TEKS NARASI “JOJO JOHAR” BERBASIS MODEL PROJECT BASED LEARNING UPAYA PENINGKATAN SIKAP KREATIF DAN KETERAMPILAN MENULIS RINGKASAN SISWA KELAS III SD NGADIRGO 03 SEMARANG - Alin Pramesti; Panca Dewi Purwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Students' low ability to summarize narrative texts is a major problem in this study, in which only 48% (13 out of 27 students) of third-grade students at Ngadirgo 03 Elementary School in Semarang met the learning completeness criteria (KKTP). This study aims to describe the steps and determine the effectiveness of Project-Based Learning (PjBL) based on the Deep Learning Model in improving students' creative attitudes and summary writing skills. This study used a sequential descriptive mixed-method design, in accordance with the stages outlined by (Khabibullah et al., 2024), combining quantitative data from KKTP scores with qualitative data from observations and interviews. The application of this model involves active project steps such as analyzing the contextual narrative text “Jojo Johar,” collaborative discussions, and producing systematic summaries. The effectiveness test results show a significant increase, marked by an increase in the average student score from 73.5 to 84.3. Additionally, the percentage of students meeting KKTP criteria increased substantially from 48% (13 students) to 85% (23 students). This improvement proves that the Deep Learning-based PjBL model is effective in strengthening summary writing skills and fostering students' creative attitudes. Keywords: Project Based Learning, Deep Learning, Creative Attitude, Summary Writing, Narrative Text